Hedgehog or fox? Theories of change for dryland cereals in Eastern Africa. (22nd December 2021) - Orr, Alastair; Muange, Elijah
Abstract: International Crops Research Institute for the Semi‐Arid Tropics' (ICRISAT) research strategy for sorghum and millets is based on market‐led development. We analyse the construction of this Theory of Change and its application to Eastern Africa using evidence from the Harnessing Opportunities for Productivity Enhancement (HOPE) project. We trace the evolution of market discourse in ICRISAT and ask why this discourse became so influential. The scale of commercialisation was limited, and its effect on intensification was mixed. A Green Revolution for dryland cereals in Eastern Africa may come not from improved varieties that give higher yields but that mature early and evade drought. A modified Theory of Change for dryland cereals requires greater recognition of household food security, farmer agency and regional heterogeneity.